A review of carbon materials for supercapacitors. (September 2022) - Zhai, Zuozhao; Zhang, Lihui; Du, Tianmin; Ren, Bin; Xu, Yuelong; Wang, Shasha; Miao, Junfeng; Liu, Zhenfa
Graphical abstract: Highlights: The energy storage mechanisms of electric double-layer supercapacitors are presented. Several commonly used supercapacitor carbon electrode materials are shown. Prospects for further research and development of the supercapacitor carbon materials. Abstract: The role of supercapacitors in the energy storage industry is gaining importance due to their high power density and long life cycle. In recent years, supercapacitors have made numerous breakthroughs. Carbon materials are the most commonly used electrode materials for supercapacitors and the researches of carbon materials are significant for developing supercapacitors. Herein, this article presents the energy storage mechanisms of supercapacitors and the commonly used carbon electrode materials. The energy storage mechanism includes commonly used energy storage models and the verification and in-depth understanding of these models using molecular dynamic simulation and in-situ technology. The carbon electrode materials section introduces the most commonly used carbon materials and their applications in the field of supercapacitors. Finally, the development trend of carbon-based supercapacitors is prospected.